2007
DOI: 10.1111/j.1365-2923.2007.02897.x
|View full text |Cite
|
Sign up to set email alerts
|

Doctor performance assessment in daily practise: does it help doctors or not? A systematic review

Abstract: There is substantial potential to assess performance of doctors in routine practise. The longterm impact and effectiveness of formative performance assessments on education and quality of care remains hardly known. Future research designs need to pay special attention to unmasking effectiveness in terms of performance improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
28

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 92 publications
(256 reference statements)
1
88
0
28
Order By: Relevance
“…A review of performance-based assessment, including the use of peer assessment, portfolio, appraisal report and medical audit, highlighted that there are 19 studies providing evidence of positive assessment effectiveness at levels 1, 2 and 3. 19 One of these studies reported the audit loop for using SAIL (Sheffield Assessment Instrument for Letters), a WBA method designed to improve the communication between secondary and primary care using referral letters, with every doctor improving their mean scores 3 months after receiving feedback on the quality of their clinic letters. 20 It is acknowledged that empirical evidence is lacking for WBA supporting an improvement in the routine practice of doctors.…”
Section: Workplace-and Competency-based Assessmentmentioning
confidence: 99%
“…A review of performance-based assessment, including the use of peer assessment, portfolio, appraisal report and medical audit, highlighted that there are 19 studies providing evidence of positive assessment effectiveness at levels 1, 2 and 3. 19 One of these studies reported the audit loop for using SAIL (Sheffield Assessment Instrument for Letters), a WBA method designed to improve the communication between secondary and primary care using referral letters, with every doctor improving their mean scores 3 months after receiving feedback on the quality of their clinic letters. 20 It is acknowledged that empirical evidence is lacking for WBA supporting an improvement in the routine practice of doctors.…”
Section: Workplace-and Competency-based Assessmentmentioning
confidence: 99%
“…12,13 Research supports the reliability of the PAR/NSPAR and other multisource feedback programs in assessing the multiple domains of medical practice 14−17 and provides evidence that the feedback enables physicians to improve performance. 15,[17][18][19][20] Yet skepticism persists about its educational and improvement impact. 20,21 Some physician participants have reported concerns that physician colleagues often had limited ability to directly observe their practice and hence to make informed and useful assessments.…”
Section: And the College Of Family Physicians Of Canada In Canada;mentioning
confidence: 99%
“…DPE undoubtedly plays an important role in ensuring the good quality of service on doctorpatient communication platforms and improving customer satisfaction and loyalty [5,6,7]. Meanwhile, doctor performance evaluation benefits the doctors owning selfimprovements on medical practice [8].…”
Section: Introductionmentioning
confidence: 99%